2021
DOI: 10.1002/acn3.51411
|View full text |Cite
|
Sign up to set email alerts
|

Nusinersen in pediatric and adult patients with type III spinal muscular atrophy

Abstract: Objective We report longitudinal data from 144 type III SMA pediatric and adult patients treated with nusinersen as part of an international effort. Methods Patients were assessed using Hammersmith Functional Motor Scale Expanded (HFMSE), Revised Upper Limb Module (RULM), and 6‐Minute Walk Test (6MWT) with a mean follow‐up of 1.83 years after nusinersen treatment. Results Over 75% of the 144 patients had a 12‐month follow‐up. There was an increase in the mean scores from baseline to 12 months on both HFMSE (1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 34 publications
2
20
0
1
Order By: Relevance
“…According to a multivariate linear regression analysis, patient age and baseline score, but not SMN2 copy number, appear to be predictive of changes in HFMSE and RULM scores [ 27 ]. These findings are generally supported by those from a cohort of 5q SMA type 3 patients aged < 18 years participating in a recent observational study [ 28 ]. Mean HFMSE and RULM scores were significantly ( p < 0.05) improved, while the mean 6MWT distance was stable after 12 months’ nusinersen therapy (respective mean change from baseline of 1.53, 1.26, and 10.32 m; mean baseline values of 43.05, 31.90, and 319.87 m) in these patients ( n = 59, 45 and 34) [ 28 ].…”
Section: Therapeutic Efficacy Of Nusinersensupporting
confidence: 78%
“…According to a multivariate linear regression analysis, patient age and baseline score, but not SMN2 copy number, appear to be predictive of changes in HFMSE and RULM scores [ 27 ]. These findings are generally supported by those from a cohort of 5q SMA type 3 patients aged < 18 years participating in a recent observational study [ 28 ]. Mean HFMSE and RULM scores were significantly ( p < 0.05) improved, while the mean 6MWT distance was stable after 12 months’ nusinersen therapy (respective mean change from baseline of 1.53, 1.26, and 10.32 m; mean baseline values of 43.05, 31.90, and 319.87 m) in these patients ( n = 59, 45 and 34) [ 28 ].…”
Section: Therapeutic Efficacy Of Nusinersensupporting
confidence: 78%
“…Twenty-fourmonth changes were also analyzed subdividing the cohort according to functional status (sitters vs. walkers), SMA type 3 subtype (3A and 3B) and according to age-bands. [15][16][17][18][19] Pearson's Correlation test was performed to measure correlation between disease duration and 24-month changes, using Cohen's conventions as interpretation.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed that approximately HFMSE has changed in 80% of untreated patients with SMA types 2 and 3 within the range of ± 2 points [17]. Over approximately 1 year observation period, one recent study demonstrated that SMA type 2 and 3 patients treated with nusinersen have a mean change of 1.53 to 3.7 in HFMSE score [13,15,25], whereas the natural history data showed a mean change of − 1.9 to − 0.56 in the non-treated population [15,17,[25][26][27]. In addition, a study focused on caregivers' point of view suggested that score gain of at least two in each HFMSE ability may justify the treatment [19].…”
Section: Discussionmentioning
confidence: 99%
“…The reason for this variability of treatment responses has been of critical interest for both patients and clinicians; however, some studies reported that the treatment initiation at an earlier stage of the disease may provide better effect [8,10], which is supported by the promising results from clinical trials of nusinersen in presymptomatic infants with SMA [11]. For patients with SMA types 2 and 3, there were reports suggesting age and baseline motor function scores were predictive of the changes in motor function after the initiation of nusinersen [12,13].…”
Section: Introductionmentioning
confidence: 99%